Victimization in Prison. A Study of Victimization and Prison Climate Dimensions in Belgian Prisons - Goossens, Elien (Victims & offenders, 2025)
Prisoner victimization introduces significant challenges to penal institutions worldwide. Researchers across the globe already provided extensive knowledge on risk factors from community crime theories for prison victimization. Other scholars are focusing on prison climate. The present study contributes to previous works by exploring both the role of community crime theory (individual, prisoner related) risk factors and prison climate dimensions in explaining prisoner victimization in Belgium. Three climate dimensions – relationships, safety and autonomy – were analyzed. Specifically, the study examined a sample of 1,006 prisoners using bivariate and multivariate regression analyses. The multivariate results showed that prison climate dimensions significantly contribute to explaining prisoner victimization, in addition to the other risk factors. These findings suggest that deprivation and strain theories remain relevant for understanding prison violence. Future researchers should study other prison climate dimensions, as well as environmental characteristics that may facilitate victimization. This paper also highlights the importance of investments in prison climate, such as dynamic security through relationships, in addition to hard security.